A Roadmap for Mainstreaming Climate Risk Management in Zambia’s Agricultural Education - Hansen, James; Dinku, Tufa; Grossi, Amanda; Kasoma-Pele, Winnie; Makungwe, Mirriam; Chinembiri, Evans; Dinh, Dannie (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Strengthening the capacity of agricultural extension and advisory services (EAS) to use available climate information services (CIS) to support farmers to better manage climate risks is an important part of the AICCRA project strategy to enhance agricultural resilience in Africa. Climate Risk Management in Agricultural Extension (CRMAE) is a suite of country-specific curricula at varying stages of co-development and adoption in five countries (Ethiopia, Senegal, Kenya, Zambia, Ghana). This brief summarizes the process to date, of co-developing and mainstreaming CRMAE in Zambia.